Alterations in mitochondrial fission, fusion, and mitophagic protein expression in the gastrocnemius of mice after a sciatic nerve transection. Issue 4 (3rd September 2018) - Graham, Zachary A.; Harlow, Lauren; Bauman, William A.; Cardozo, Christopher P.
ABSTRACT: Introduction: Paralysis and unloading of skeletal muscle leads to a rapid loss in muscle size, function and oxidative capacity. The reduction in metabolic capability after disuse leads to dysregulation and increased breakdown of mitochondria by mitophagy. Methods: Eight‐week‐old C57BL/6 male mice were given a sham surgery or sciatic nerve transection. Animals were euthanized at 7, 14, 21, or 35 days postsurgery. Whole gastrocnemius muscles were isolated from the animal, weighed and used for Western blotting. Results: Markers of mitochondrial fusion were reduced while fission proteins were elevated following a sciatic nerve transection. There were elevations in phosphorylated unc‐51‐like kinase 1 (ULK1 S555 ) and total expression of Beclin1, and of the mitophagy markers PINK1, p62, and microtubule‐associated proteins 1A/1B light chain 3b (LC3‐II). Conclusions: Paralysis of the gastrocnemius leads to a progressive elevation in expression of mitochondrial fission and mitophagic proteins. Rehabilitative or pharmaceutical interventions to limit excess mitophagy may be effective therapies to protect paralyzed muscle mass and function. Muscle Nerve 58 : 592–599, 2018